Low-dose inorganic arsenic exposure reprograms macrophages differentiation and function toward tumor-promoting phenotypes - Emily J. Illingworth; Sylvia S. Sanchez; Kristal A. Rychlik; Andre Kleensang; Jason Laird; Gabriel A. Lopez-Cecetaite; M. Carolina Rodriguez Steube; Aakriti Mathur; Pritam Sadhukhan; Daniel A. Medina-Cleghorn; Daniel Nomura; Martyn T. Smith; et al. (Environmental Research, 2026)

Aboveground insect herbivory shapes plant–soil feedback and ecosystem resilience - Nishu; Kavita Verma; S. Aneeqa Noor; Vartika Mathur (Biologia Futura, 2026)
The interaction between plants and their surrounding soil ecosystems is complex, with plant–soil feedback acting as legacy effects from previous plants, influencing subsequent plant growth and insect interactions. Recent studies have shown that experiments focusing on individual factors in isolation do not accurately predict the outcomes of these complex interactions. Aboveground herbivores impact the development of root exudates and their surrounding microbiome, suggesting that herbivory indirectly shapes belowground biotic communities. Such impact of insect herbivory on plant–soil feedback is a crucial area of ecological research. Most studies focus on root-associated organisms and their influence on foliar herbivorous insects, and little attention has been given to the reverse interaction-how foliar herbivory affects the soil environment and PSF. This study explores the bidirectional influence of herbivory and PSF, revealing that aboveground insect herbivory can significantly alter plant–soil feedback mechanisms, influencing not only plant performance but also the broader community structure. A holistic approach that integrates soil microbial complexity with insect herbivory is needed to better predict community-level outcomes and enhance plant protection strategies. Our study thus highlighted the need for a community-based perspective when studying interactions among plants, insects and soil microorganisms.

Prenatal arsenic exposure and gene expression in fetal liver, heart, lung, and placenta - Kristal A. Rychlik; Sylvia S. Sanchez; Chloe Kashiwagi; Jin-Shiung Liao; Aakriti Mathur; Emily J. Illingworth; Andre Kleensang; Alexandra Maertens; Fenna C.M. Sillé (Toxicology, 2026)

Stronger Together: The Role of the Community Dietitian in Supporting Families Affected by Alzheimer’s and Other Dementias - L. Hughes; S. Mathur; M. Kane; K. Cullinen (Journal of the Academy of Nutrition and Dietetics, 2025)

Development of a Power Operated Fenugreek Thresher - C. Naveen Kumar; R. K. Rathod; T. Nageshkumar; S. M. Mathur (Agricultural Research, 2025)

Treatment of textile effluent by electrocoagulation in a novel reactor to mitigate environmental pollution - P. Agarwal; V. K. Sangal; S. Mathur (International Journal of Environmental Science and Technology, 2025)

Step Wells of Jodhpur, Western Rajasthan, India: Implication for Hydro-geosites and Hydro-geotourism - Shiv Singh Rathore; Saurabh Mathur; S. C. Mathur (Geoheritage, 2024)

Defensive glands in Stylotermitidae (Blattodea, Isoptera) - Himanshu Thakur; Surbhi Agarwal; Aleš Buček; Jaromír Hradecký; Hana Sehadová; Vartika Mathur; Ulugbek Togaev; Thomas van de Kamp; Elias Hamann; Ren-Han Liu; Kuldeep S. Verma; Hou-Feng Li; et al. (Arthropod Structure & Development, 2024)

Three Dimensional Bioprinting for Hepatic Tissue Engineering: From In Vitro Models to Clinical Applications - Meghana Kasturi; Vidhi Mathur; Mrunmayi Gadre; Varadharajan Srinivasan; Kirthanashri S. Vasanthan (Tissue Engineering and Regenerative Medicine, 2024)
Fabrication of functional organs is the holy grail of tissue engineering and the possibilities of repairing a partial or complete liver to treat chronic liver disorders are discussed in this review. Liver is the largest gland in the human body and plays a responsible role in majority of metabolic function and processes. Chronic liver disease is one of the leading causes of death globally and the current treatment strategy of organ transplantation holds its own demerits. Hence there is a need to develop an in vitro liver model that mimics the native microenvironment. The developed model should be a reliable to understand the pathogenesis, screen drugs and assist to repair and replace the damaged liver. The three-dimensional bioprinting is a promising technology that recreates in vivo alike in vitro model for transplantation, which is the goal of tissue engineers. The technology has great potential due to its precise control and its ability to homogeneously distribute cells on all layers in a complex structure. This review gives an overview of liver tissue engineering with a special focus on 3D bioprinting and bioinks for liver disease modelling and drug screening.

Assessment and Threat to Significant Geoheritage of Soorsagar Formation of Jodhpur Group of Marwar Supergroup, Western Rajasthan, India: A Geological and Remote Sensing Approach - Saurabh Mathur; Sudhanshu Sharma; S. K. Singh; M. G. Thakkar; Gaurav Chauhan; Shiv Singh Rathore; S. C. Mathur (Geoheritage, 2023)

The Trail-Following Communication in Stylotermes faveolus and S. halumicus (Blattodea, Isoptera, Stylotermitidae) - Himanshu Thakur; Surbhi Agarwal; Jaromír Hradecký; Garima Sharma; Hou-Feng Li; Shang-En Yang; Hana Sehadová; Ravinder S. Chandel; Mirek Hyliš; Vartika Mathur; Jan Šobotník; David Sillam-Dussès (Journal of Chemical Ecology, 2023)

Mutation spectrum and enzyme profiling of G6PD deficiency in neonates of north India: a prospective study - Upasana Bhattacharyya; Preeti Deswal; Sunil Kumar Polipalli; Diksha Sharma; Manpreet Kaur; Madhulika Kabra; Neerja Gupta; Ramesh Agarwal; A. K. Deorari; V. K. Paul; Shevendru Roy; R. K. Sanjeev; et al. (Journal of Genetics, 2023)

Late Cretaceous–Early Paleocene Geodiversity of Fatehgarh Formation of Petroliferous Barmer Basin, Western Rajasthan, India: A Potential Geopark Site - Saurabh Mathur; Sudhanshu Sharma; S. K. Singh; S. S. Rathore; S. C. Mathur (Geoheritage, 2023)

Assessing the environmental impact due to photolytic degradation of ethane-bis(pentabromophenyl) in plastics - Rajeev S. Mathur; Bijay Banstola; Kelsey M. Lopez; Mark W. Beach; Daniel De Schryver (Chemosphere, 2023)

Investigation of metasomatism using Cu, Zn and Fe stable isotopes: Rodingitization of mafic and ultramafic rocks in ophiolites from northern Greece - N. Zaronikola; V. Debaille; A. Rogkala; P. Petrounias; R. Mathur; S. Decrée; P. Pomonis; K. Hatzipanagiotou; B. Tsikouras (Lithos, 2023)

Correction to: Qualitative Assessment of Geoheritage for Geotourism Promotion: a Case Study from Mehrangarh Ridge in Jodhpur City, Western Rajasthan, India - Mathur Saurabh; Sharma Sudhanshu; Singh S. K.; Mathur S. C. (Geoheritage, 2021)

Qualitative Assessment of Geoheritage for Geotourism Promotion: a Case Study from Mehrangarh Ridge in Jodhpur City, Western Rajasthan, India - Mathur Saurabh; Sharma Sudhanshu; Singh S. K.; Mathur S. C. (Geoheritage, 2021)

Decolorization of malachite green dye from aqueous solution using biosurfactant-stabilized iron oxide nanoparticles: process optimization and reaction kinetics - B. Sharma; S. Menon; S. Mathur; N. Kumari; V. Sharma (International Journal of Environmental Science and Technology, 2021)

Metabolic changes in triple negative breast cancer-focus on aerobic glycolysis - J. R. Dev Arundhathi; Sandeep R Mathur; Ajay Gogia; S. V. S. Deo; Purusottam Mohapatra; Chandra Prakash Prasad (Molecular Biology Reports, 2021)

Comparing transformation pathways across major economies - R. Schaeffer; A. Köberle; H. L. van Soest; C. Bertram; G. Luderer; K. Riahi; V. Krey; D. P. van Vuuren; E. Kriegler; S. Fujimori; W. Chen; C. He; et al. (Climatic Change, 2020)

Development of pepper vein banding virus chimeric virus-like particles for potential diagnostic and therapeutic applications - Pallavi Sabharwal; C. Sushmitha; C. K. Amritha; Usha Natraj; Mathur R. N. Murthy; Handanahal S. Savithri (Archives of Virology, 2020)

Assessment of litter availability and its quality plasticity of four wild species of the Indian arid environment - Manish Mathur; Manohar Singh Suthar; Praveen Gehlot; S. Sundaramoorthy (Tropical Ecology, 2019)

Modelling of co-occurrence patterns of grassland species: reciprocal shifting between competition and facilitation - Manish Mathur; S. Sundaramoorthy (Tropical Ecology, 2019)

Toxicity assessment of popular baby skin care products from Indian market using microbial bioassays and chemical methods - A. Nepalia; A. Singh; N. Mathur; S. Pareek (International Journal of Environmental Science and Technology, 2018)

Feasibility study of waste (d) potential: co-digestion of organic wastes, synergistic effect and kinetics of biogas production - K. Paritosh; S. Mathur; N. Pareek; V. Vivekanand (International Journal of Environmental Science and Technology, 2018)

Gene networks for total number born in pigs across divergent environments - Lucas L. Verardo; Marcos S. Lopes; Pramod Mathur; Ole Madsen; Fabyano F. Silva; Martien A. M. Groenen; Egbert F. Knol; Paulo S. Lopes; Simone E. F. Guimarães (Mammalian Genome, 2017)

Assessment of heavy metal contamination of road dusts from industrial areas of Hyderabad, India - Ramavati Mathur; V. Balaram; M. Satyanarayanan; S. S. Sawant (Environmental Monitoring and Assessment, 2016)

Potential of Crop Residue and Fertilizer on Enrichment of Carbon Pools in Upland Soils of Subtropical India - P. K. Ghosh; K. K. Hazra; M. S. Venkatesh; K. K. Singh; Narendra Kumar; R. S. Mathur (Agricultural Research, 2016)

Investigating deleterious effects of ultraviolet (UV) radiations on wheat by a quick method - S. Mathur; Anjana Jajoo (Acta Physiologiae Plantarum, 2015)

Monitoring hospital wastewaters for their probable genotoxicity and mutagenicity - Pratibha Sharma; N. Mathur; A. Singh; M. Sogani; P. Bhatnagar; R. Atri; S. Pareek (Environmental Monitoring and Assessment, 2015)

A multi-step phosphorelay two-component system impacts on tolerance against dehydration stress in common wheat - Vijay Gahlaut; Saloni Mathur; Raman Dhariwal; Jitendra P. Khurana; Akhilesh K. Tyagi; Harindra S. Balyan; Pushpendra K. Gupta (Functional & Integrative Genomics, 2014)

The N-terminal region containing the zinc finger domain of tobacco streak virus coat protein is essential for the formation of virus-like particles - Chhavi Mathur; Kalyani Mohan; T. R. Usha Rani; M. Krishna Reddy; Handanahal S. Savithri (Archives of Virology, 2014)

Particulate matter concentration in ambient air and its effects on lung functions among residents in the National Capital Region, India - C. Kesavachandran; B. S. Pangtey; V. Bihari; M. Fareed; M. K. Pathak; A. K. Srivastava; N. Mathur (Environmental Monitoring and Assessment, 2013)

Pathogen-derived resistance using a viral nucleocapsid gene confers only partial non-durable protection in peanut against peanut bud necrosis virus - S. Chander Rao; P. Bhatnagar-Mathur; P. Lava Kumar; A. Sudarshan Reddy; Kiran K. Sharma (Archives of Virology, 2013)

Modeling, docking, simulation, and inhibitory activity of the benzimidazole analogue against β-tubulin protein from Brugia malayi for treating lymphatic filariasis - Om Prakash Sharma; Archana Pan; S. L. Hoti; Ankush Jadhav; Muthu Kannan; Premendu P. Mathur (Medicinal Chemistry Research, 2012)

Opsonization, Biodistribution, Cellular Uptake and Apoptosis Study of PEGylated PBCA Nanoparticle as Potential Drug Delivery Carrier - Kiran Ramanlal Chaudhari; Mukesh Ukawala; Arehalli S. Manjappa; Abhinesh Kumar; Piyush Kishor Mundada; Anil Kumar Mishra; Rashi Mathur; Jukka Mönkkönen; Rayasa S. Ramchandra Murthy (Pharmaceutical Research, 2012)

Erratum to: Opsonization, Biodistribution, Cellular Uptake and Apoptosis Study of PEGylated PBCA Nanoparticle as Potential Drug Delivery Carrier - Kiran Ramanlal Chaudhari; Mukesh Ukawala; Arehalli S. Manjappa; Abhinesh Kumar; Piyush Kishor Mundada; Anil Kumar Mishra; Rashi Mathur; Jukka Mönkkönen; Rayasa S. Ramchandra Murthy (Pharmaceutical Research, 2011)

Glycyrrhiza glabra (Linn.) and Lavandula officinalis (L.) cell suspension cultures-based biotransformation of β-artemether - Suman Patel; Rashmi Gaur; Mohita Upadhyaya; Archana Mathur; Ajay K. Mathur; Rajendra S. Bhakuni (Journal of Natural Medicines, 2011)

Carbon isotope excursion at Paleocene–Eocene transition in Jaisalmer Basin, western Rajasthan, India - Anil Maheshwari; A. N. Sial; S. C. Mathur; Amita Tripathi (Carbonates and Evaporites, 2010)

Identification of quantitative trait loci associated with resistance to foliar diseases in sorghum [Sorghum bicolor (L.) Moench] - S. Murali Mohan; R. Madhusudhana; K. Mathur; D. V. N. Chakravarthi; Sanjay Rathore; R. Nagaraja Reddy; K. Satish; G. Srinivas; N. Sarada Mani; N. Seetharama (Euphytica, 2010)

Biotransformation of artemisinin using cell suspension cultures of Catharanthus roseus (L.) G.Don and Lavandula officinalis L. - Suman Patel; Rashmi Gaur; Priyanka Verma; Rajendra S. Bhakuni; Archana Mathur (Biotechnology Letters, 2010)

Influence of cellular differentiation and elicitation on intermediate and late steps of terpenoid indole alkaloid biosynthesis in Catharanthus roseus - Ashutosh K. Shukla; Ajit K. Shasany; Ram K. Verma; Madan M. Gupta; Ajay K. Mathur; Suman P. S. Khanuja (Protoplasma, 2010)

Development of isopluvial map using L-moment approach for Tehri-Garhwal Himalaya - S. Sarkar; N. K. Goel; B. S. Mathur (Stochastic Environmental Research and Risk Assessment, 2010)

Variation of Mo isotopes from molybdenite in high-temperature hydrothermal ore deposits - Ryan Mathur; S. Brantley; A. Anbar; F. Munizaga; V. Maksaev; R. Newberry; J. Vervoort; G. Hart (Mineralium Deposita, 2010)

Toward a Fuzzy Logic Control of the Infant Incubator - Narender P. Reddy; Garima Mathur; S. I. Hariharan (Annals of Biomedical Engineering, 2009)

Comparative Analysis of RAPD and ISSR Markers for Characterization of Sesame (Sesamum indicum L) Genotypes - S. N. Sharma; Vinod Kumar; Shivangi Mathur (Journal of Plant Biochemistry and Biotechnology, 2009)

Transient inhibitory effect of methoxychlor on testicular steroidogenesis in rat: an in vivo study - S. Vaithinathan; B. Saradha; P. P. Mathur (Archives of Toxicology, 2008)

CD38/Cyclic ADP-Ribose Regulates Astrocyte Calcium Signaling: Implications for Neuroinflammation and HIV-1-Associated Dementia - Sugato Banerjee; Timothy F. Walseth; Kathleen Borgmann; Li Wu; Keshore R. Bidasee; Mathur S. Kannan; Anuja Ghorpade (Journal of Neuroimmune Pharmacology, 2008)

Assessment and rationalization of genetic diversity of Papua New Guinea taro (Colocasia esculenta) using SSR DNA fingerprinting - D. Singh; E. S. Mace; I. D. Godwin; P. N. Mathur; T. Okpul; M. Taylor; D. Hunter; R. Kambuou; V. Ramanatha Rao; G. Jackson (Genetic Resources and Crop Evolution, 2008)

Event-based Sediment Yield Modeling using Artificial Neural Network - Raveendra K. Rai; B. S. Mathur (Water Resources Management, 2008)

Blood Levels of Polycyclic Aromatic Hydrocarbons in Children of Lucknow, India - Vipul K. Singh; Devendra K. Patel; S. Ram; N. Mathur; M. K. J. Siddiqui; Jai Raj Behari (Archives of Environmental Contamination and Toxicology, 2008)

Studies on the Genotoxicity of Endosulfan in Different Tissues of Fresh Water Fish Mystus vittatus Using the Comet Assay - Shilpi Sharma; N. S. Nagpure; Ravindra Kumar; Sanjay Pandey; Satish K. Srivastava; Poonam J. Singh; P. K. Mathur (Archives of Environmental Contamination and Toxicology, 2007)

Type-2 diabetes related intermediate phenotypic traits in north Indian diabetics - S. K. Mathur; Piyush Chandra; Sandhya Mishra; Peeyush Ajmera; Praveen Sharma (Indian Journal of Clinical Biochemistry, 2007)

Behavior of β-Cyfluthrin after Foliar Application on Chickpea (cicer aretinium L. ) and Pigeon Pea (cajanus cajan L.) - I. Mukherjee; M. Gopal; D. S. Mathur (Bulletin of Environmental Contamination and Toxicology, 2007)

Himalayan glacier retreat using IRS 1C PAN stereo data - I. M. Bahuguna; A. V. Kulkarni; Shailesh Nayak; B. P. Rathore; H. S. Negi; P. Mathur (International Journal of Remote Sensing, 2007)

Preventive and Curative Biological Treatments for Control of Botrytis cinerea Stem Canker of Greenhouse Tomatoes - R. S. Utkhede; S. Mathur (BioControl, 2006)

Genotyping of urinary and fecal Proteus mirabilis isolates from individuals with long-term urinary catheters - S. Mathur; N. A. Sabbuba; M. T. E. Suller; D. J. Stickler; R. C. L. Feneley (European Journal of Clinical Microbiology & Infectious Diseases, 2005)

Change detection study for snow covered mountains using remote sensing and ground based measurements - H. S. Negi; V. D. Mishra; P. Mathur (Journal of the Indian Society of Remote Sensing, 2005)

Toxic Effects of Textile Printing Industry Effluents on Liver and Testes of Albino Rats - R. Krishnatrey; S. Sharma; K. P. Sharma; N. Mathur (Bulletin of Environmental Contamination and Toxicology, 2003)

Carbon and oxygen isotope profiles from the terminal precambrian Marwar Supergroup, Rajasthan, India - Anil Maheshwari; A. N. Sial; S. C. Mathur (Carbonates and Evaporites, 2003)

Persistent chlorinated pesticides and intra-uterine foetal growth retardation: a possible association - M. Siddiqui; S. Srivastava; S. Srivastava; P. Mehrotra; N. Mathur; I. Tandon (International Archives of Occupational and Environmental Health, 2003)

Intercomparison of IRS-P4-MSMR derived geophysical products with DMSP-SSM/I and TRMM-TMI finished products - A. K. Varma; R. M. Gairola; A. K. Mathur; B. S. Gohil; Vijay K. Agarwal (Journal of Earth System Science, 2002)

Rain rate measurements over global oceans from IRS-P4 MSMR - A. K. Varma; R. M. Gairola; Samir Pokhrel; B. S. Gohil; A. K. Mathur; Vijay K. Agarwal (Journal of Earth System Science, 2002)

Molecular analysis of two complete rice tungro bacilliform virus genomic sequences from India - N. Nath; S. Mathur; I. Dasgupta (Archives of Virology, 2002)

Cloning and characterization of an insecticidal crystal protein gene fromBacillus thuringiensis subspecieskenyae - Hari S. Misra; Nivedita P. Khairnar; Manjula Mathur; N. Vijayalakshmi; Ramesh S. Hire; T. K. Dongre; S. K. Mahajan (Journal of Genetics, 2002)

A Social Approach to the Validation of Traditional Veterinary Remedies – The Anthra Project - N.S. Ghotge; S.R. Ramdas; S. Ashalata; N.P. Mathur; V.G. Broome; M.L. Sanyasi Rao (Tropical Animal Health and Production, 2002)

Field based spectral reflectance studies to develop NDSI method for snow cover monitoring - A V Kulkarni; J Srinivasulu; S S Manjul; Mathur P (Journal of the Indian Society of Remote Sensing, 2002)

Carbon isotope fluctuations through the neoproterozoic-lower Cambrian Birmania basin, Rajasthan, India - Anil Maheshwari; A. N. Sial; S. C. Mathur (Carbonates and Evaporites, 2002)

Ameliorative effects of proline on salt stress-induced lipid peroxidation in cell lines of groundnut (Arachis hypogaea L.) - M. Jain; G. Mathur; S. Koul; N. Sarin (Plant Cell Reports, 2001)

Polychlorinated Dibenzo-p-Dioxins and Dibenzofurans in Storm Water Outfalls Adjacent to Urban Areas and Petroleum Refineries in San Francisco Bay, California - R. J. Wenning; D. B. Mathur; D. J. Paustenbach; M. J. Stephenson; S. Folwarkow; W. J. Luksemburg (Archives of Environmental Contamination and Toxicology, 1999)

Isolation of two antifungal compounds fromNeolitsea cuipala and their activity against some plant pathogenic fungi - P. Boruah; P. Deka Bhuyan; S. C. Dutta; S. Mohan; R. K. Mathur (Folia Microbiologica, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Thymopentin and splenopentin as immunomodulators - Vijay K. Singh; Sumita Biswas; Krishna B. Mathur; Wahajul Haq; Satyendra K. Garg; Shyam S. Agarwal (Immunologic Research, 1998)

Biochemical and morphological changes in some organs of rats in nickel intoxication - A. K. Mathur; Satya V. Chandra; Jairaj Behari; S. K. Tandon (Archives of Toxicology, 1977)